2021
DOI: 10.3389/fpls.2021.773118
|View full text |Cite
|
Sign up to set email alerts
|

The Economics Spectrum Drives Root Trait Strategies in Mediterranean Vegetation

Abstract: Extensive research efforts are devoted to understand fine root trait variation and to confirm the existence of a belowground root economics spectrum (RES) from acquisitive to conservative root strategies that is analogous to the leaf economics spectrum (LES). The economics spectrum implies a trade-off between maximizing resource acquisition and productivity or maximizing resource conservation and longevity; however, this theoretical framework still remains controversial for roots. We compiled a database of 320… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…Such discrepancy between them may be related to two possible reasons. First, RD was negatively related to RTD for woody species, which is in line with previous studies reporting a trade-off between RD and RTD in Mediterranean woody plants (de la Riva et al, 2016b(de la Riva et al, , 2021a. As mentioned above, such a negative relationship can be explained by the anatomical tradeoffs between RD and RTD.…”
Section: Plant Growth Formsupporting
confidence: 90%
See 4 more Smart Citations
“…Such discrepancy between them may be related to two possible reasons. First, RD was negatively related to RTD for woody species, which is in line with previous studies reporting a trade-off between RD and RTD in Mediterranean woody plants (de la Riva et al, 2016b(de la Riva et al, , 2021a. As mentioned above, such a negative relationship can be explained by the anatomical tradeoffs between RD and RTD.…”
Section: Plant Growth Formsupporting
confidence: 90%
“…For example, RD was negatively associated with RTD in the tropical and subtropical forests, which is consistent with the study of Valverde-Barrantes et al (2021). Such a negative relationship can be explained by the anatomical relationships that is commonly observed in leaves (Laughlin, 2014;de la Riva et al, 2016a), plants can have similar specific leaf area (or SRL) values with different proportional investments in leaf tissue density (or RTD) and leaf thickness (or RD) (John et al, 2017;de la Riva et al, 2021a), which would depend on the species identity and their environmental conditions (Olmo et al, 2014).We found that RTD was negatively related to SRL in the temperate forest, suggesting the tradeoff between resource acquisition and construction costs of roots (Eissenstat et al, 2000). From the cost-benefit theory, roots with higher SRL and lower RTD would have lower construction costs, higher metabolic rates and faster return of investments (de la Riva et al, 2021b).…”
Section: Biomesupporting
confidence: 83%
See 3 more Smart Citations